The City of Orik in the Writings of Ancient Authors and Archaeological Records - Aleks Trushaj; Gladiola Elezi (Acta Universitatis Lodziensis: Folia Archaeologica)
The ancient Illyrian port city of Orik, located in what is now Albania, was an important maritime and Cultural Centre in the Adriatic region. This study provides a comprehensive analysis of all available ancient textual evidence of Orik, tracing its evolution from the 5th century BCE to late antiquity. The examination of these written sources is crucial for reconstructing the history and topography of Orik, which cannot be fully identified only by archaeological data. The main purpose of the study is to systematically identify, collect, and analyse every mention of Orik in ancient studies, including the studies of Herodotus, Pseudo-Skilax, Strabo, Titus Livius. To obtain precise and objective conclusions, a rigorous methodology was applied, which includes source criticism, comparative analysis, and correlation with archaeological data. The study provides valuable information about the evolution of Orik’s functions and status over time, its fortifications, economic activities, religious objects, and more. It allows for tracing how the knowledge of ancient geographers about this border town developed and how Greco-Roman authors portrayed it in their narratives. The most innovative contribution of the study is the first comprehensive investigation of the entire body of textual evidence about Orik. This holistic synthesis enables a deeper reconstruction of this influential Adriatic settlement. The results enhance understanding of ancient Illyria and the complex dynamics of its Hellenization. They are beneficial for related research and education. Overall, by systematically collecting and critically analysing all available ancient sources, this study offers a multi-layered portrait of Orik as a strategic Greek colony, Illyrian stronghold, maritime trade hub, and crossroads of cultural fusion in the Adriatic.